Short-axon cells in the olfactory bulb: dendrodendritic synaptic interactions. - Getchell, T V (1975)
1. In the rabbit olfactory bulb, analysis has been carried out of extracellular unitary responses in the glomerular layer to olfactory nerve volleys. 2. Units in the glomerular layer responded to single volleys with single, double, triple or longer repetitive spike discharges. The shortest initial latencies are consistent with monosynaptic excitation from the olfactory nerves; longer latencies may reflect longer nerve pathways or polysynaptic connexions in the glomerular layer. 3. Like mitral and tufted cells, some glomerular layer units gave evidence of activation by discrete nerve bundles. This correlates with recent anatomical evidence for projections of discrete olfactory nerve bundles to the glomeruli. 4. Facilitation of glomerular layer units took the form of lower spike thresholds and shorter latencies, when testing with paired olfactory nerve volleys of weak strength at relatively short intervals (less than 40 msec). Supression took the form of raised thresholds, longer latencies and briefer repetitive discharges; this was particularly evident with strong volleys at long testing intervals. 5. The early period of facilitation and later period of suppression did not correlate with the recovery cycle of the olfactory nerves; the nerves had an absolute refractory period of approximately 3 msec, relative refractory period of 15-30 msec, and a small supernormal period of several hundred msec or more. 6. The evidence that the facilitation and suppression are mediated by dendrodendritic pathways through the periglomerular short-axon cells is discussed in relation to recent electronmicroscopical studies. The results have implications for similar pathways through short-axon cell dendrites in other parts of the nervous system.